Morphological investigation and description of two new Gomphonema Ehrenberg (Bacillariophyta) species from India and Vietnam with biogeographical comments - Pardhi, Samadhan; Vigneshwaran, Anbukkarasu; Kociolek, J. Patrick; Glushchenko, Anton; Kulikovskiy, Maxim; Karthick, Balasubramanian (Phytotaxa, 2020)
Two new species of Gomphonema Ehrenberg are described based on light and scanning electron microscopical observations. These are Gomphonema kallarense sp. nov. found in India and G. kezlyae sp. nov. found in India and Vietnam. We also report and document the morphology and variability of G. doonense from Vietnam, a species previously described from India based on a limited number of valves. Both G. doonense and G. kallarense have striae composed of doubly-punctate striae that are without occlusions, while G. kezlyae has striae with single rows of areolae that have external occlusions giving the impression of C-shaped openings. Our investigation shows that India and Vietnam share some species in common, adding additional evidence that the biogeography of freshwater diatoms from the tropics warrants future investigation.